(untitled) (Pulse, 2018)
Obstructive sleep apnea (OSA) is characterized by repetitive airflow reduction caused by collapse of the upper airway during sleep in addition to daytime sleepiness, clinical symptoms include fatigue, insomnia, and snoring. The condition is associated with adverse clinical outcomes, including cardiovascular disease, hypertension, cognitive impairment, and metabolic abnormalities.1 Among the risk factors for OSA, obesity is probably the most important. Several studies have consistently found an association between increased body weight and risk of OSA. Tomographic scanned images have shown that obesity causes increased fatty deposits in the pharyngeal area.2 The deposits encroach on the airway and contribute to airway narrowing. Also, among obese patients as compared to normal controls, fat deposits appear to alter the shape of the upper airway without necessarily reducing the cross-sectional area. M. A. Ciscar et al used magnetic resonance imaging to investigate differences between obese and normal controls.2 Ultrafast magnetic resonance imaging was used to study the upper airway and surrounding soft tissue in 17 patients with OSA during wakefulness and sleep, and in eight healthy subjects whilst awake. Coronal sections of awake OSA patients showed elliptical-shaped airways with long axes that were oriented anteroposterior; normal controls had airways that were oriented transversely. Studies using computed tomography have produced similar results.14 Pulse Vol.10 January-December 2017 p.38-41